2005
DOI: 10.1177/08830738050200110501
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Primary Epileptogenic Hemisphere from Electroencephalographic (EEG) and Magnetoencephalographic Dipole Lateralizations in Children With Intractable Epilepsy

Abstract: We used electroencephalographic (EEG) and magnetoencephalographic dipole lateralizations to identify the primary epileptogenic hemisphere in 41 children with intractable localization-related epilepsy. We compared EEG and magnetoencephalographic dipole lateralizations, EEG ictal onsets, and magnetic resonance images (MRIs). Concordant lateralization of EEG and magnetoencephalographic dipoles (> 50% of each lateralizing to the same hemisphere) occurred in 34 patients, with EEG ictal onsets in the same hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Localization was also satisfactory at the level of the anatomical region because the MEG spike sources were distributed exactly at or in the vicinity of the lesion in most patients. The hemispheric lateralization rate is similar to or higher than that reported for patients with intractable focal epilepsy in previous studies: 68% (when compared to brain MRI and intracranial ictal onset zone) (12), 82% (lobar concordance to anatomical lesional in brain MRI) (7), and 89% (when compared to the final surgical decision) (4). The lobar or regional localization rate is similar to the 72% rate reported in patients with intractable focal epilepsy (7).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Localization was also satisfactory at the level of the anatomical region because the MEG spike sources were distributed exactly at or in the vicinity of the lesion in most patients. The hemispheric lateralization rate is similar to or higher than that reported for patients with intractable focal epilepsy in previous studies: 68% (when compared to brain MRI and intracranial ictal onset zone) (12), 82% (lobar concordance to anatomical lesional in brain MRI) (7), and 89% (when compared to the final surgical decision) (4). The lobar or regional localization rate is similar to the 72% rate reported in patients with intractable focal epilepsy (7).…”
Section: Discussionsupporting
confidence: 83%
“…Removal of the dysplastic cortex that has not been characterized by brain imaging but by MEG was required for complete seizure freedom (13). In cases of discordant presurgical evaluation, concordant lateralization was related to good seizure control (12). Multiple MEG spike source clusters required identification of the multiple or extensive epileptogenic zone prior to accurate localization and delineation of the resection margin (21).…”
Section: Discussionmentioning
confidence: 99%
“…In our unit, we use a combination of MEG, and ictal and interictal video EEG to assist in the localization of the epileptogenic zone. Concordance between the scalp video EEG and MEG findings provides strong noninvasive evidence that surgical resection will be successful [9].…”
Section: Electrophysiological Investigations N Eeg and Video Eegmentioning
confidence: 98%
“…In a recent study, brain PET was also found to be a useful predictor of seizure outcome after hemispherectomy, bilateral PET abnormalities being associated with post-operative seizure recurrence [6]. Successful use of ictal SPECT for early seizure propagation [43][44][45], Magnetoencephalography (MEG) for source localization of interictal spikes [46,47] and mapping of language and motor function with functional MRI (fMRI) [48,49] are increasingly been reported. However, it remains to be seen if these techniques will independently expand the selection of pediatric surgical candidates, obviate the need for long-term invasive video EEG recordings, and improve the long term surgical outcome in children.…”
Section: When -Epilepsy Surgery?mentioning
confidence: 99%